A PILOT STUDY ON THE ROLE OF BUSINESS SCHOOLS IN ENHANCING ENTREPRENEURSHIP SKILLS FOR MBA STUDENTS - Kulkarni, Hrishikesh S.; Meshram, Meeta M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This pilot study investigates the role of business schools in fostering entrepreneurship skills among MBA students. As entrepreneurship gains prominence as a viable career path, academic institutions are increasingly expected to equip students with not just theoretical knowledge but also practical capabilities to initiate and manage ventures. This research involved the administration of a structured questionnaire consisting of 30 Likert-scale items designed to measure students’ perceptions of their business school’s contribution to various entrepreneurial competencies, such as innovation, risk-taking, leadership, business planning, and resource mobilization. The study collected responses from 40 MBA students across private business schools in the Pune region. Data were analyzed using Cronbach’s Alpha to assess internal reliability. The coefficient obtained was 0.936, indicating excellent internal consistency. The results provide foundational insights into how effectively business schools are perceived to support entrepreneurial skill development and highlight areas for curricular and pedagogical improvement.